STATUS FISIOLOGIS TERNAK SAPI BALI (Bos sondaicus) BETINA YANG DIPELIHARA PADA LAHAN GAMBUT (Physiological Status of Bali Cattle (Bos sondaicus)Maintained on Peatlands): Amiano, K.,1*) Satata, B.,1) Imanuel, R.,1) - Admin journal (AgriPeat, 2018)
ABSTRACTThe study aimed to determine the extent of the physiological status of Balinese cattle (Bossondaicus) females maintained on peatlands including environmental temperature, respiratoryfrequency, body temperature, pulse rate, and rumination which is important to know the healthstatus of female Balinese cattle. This study used 10 female Balinese cows with an average bodyweight of 300 kg and age ranged from> 24-36 months, non-pregnant status. Physiological statusmeasurements were carried out in the morning, afternoon and evening. This study uses descriptivemethods and direct observation with data processing in analysis and tabulation. Research has beencarried out at the Joint Work Group of Taruna Taruna, Tanjung Taruna Village, Jabiren RayaDistrict, Pulang Pisau Regency. The research began on January 1, 2018 to February 2, 2018. Theresults showed that the average cage temperature in the morning was 28.0 0C and humidity was79.4%. While during the day the temperature of the cage is 33.8 oC and humidity is 58.7% and inthe afternoon the temperature of the cage is 30.0 0C and 73.6%. The average respiration frequencyof female Balinese cattle in the morning is 21.1 times per minute, while during the day is 24.3times per minute and in the afternoon is 24.5 times per minute. The average body temperature offemale Balinese cattle in the morning is 37.4 0C, during the day is 38.1 0C and in the afternoon is38.2 0C. The average pulse rate of Bali cattle, in the morning is 60.3 times per minute, during theday is 65.2 times per minute while in the afternoon is 63.7 times per minute. The averagerumination in the morning was 55.2 times chewing in 31.9 seconds, during the day the averagerumination was 55.3 times chewed in 31.7 seconds while on the afternoon the average ruminationwas 55, 3 times chew in 31.8 seconds. The physiological status of Bali cattle is respiratoryfrequency, body temperature, and pulse are in normal conditions. The condition of the ambienttemperature exceeds the normal threshold and the rumination in cattle is very high this conditiondoes not cause health problemsKeywords: Bali Cattle, Micro Climate, Physiological Response